Multicenter Study of Clinical Presentation, Treatment, and Outcome in 41 Dogs With Spinal Epidural Empyema - Laws, Emma J.; Sánchez, Lluís; Beltran, Elsa; Domínguez, Elisabet; Ekiri, Abel B.; Brocal, Josep; De Risio, Luisa (Frontiers in Veterinary Science, 2022)
There is limited information on canine spinal epidural empyema (SEE). The aim of this multicenter retrospective study is to describe the clinical presentation and outcome of dogs undergoing spinal surgery or conservative management for SEE. Forty-one dogs met the inclusion criteria; the SEE was treated surgically in 17 dogs and conservatively in 24 dogs. Two dogs underwent spinal surgery after failure of conservative management, meaning that 19 dogs in total had spinal surgery. Long-term (i.e., >6 months) follow-up was available in 35 dogs (19 conservatively treated and 16 surgically treated dogs). Recovery to a functional pet status was achieved in 15/19 (78.9%) conservatively treated and 12/16 (75%) surgically treated dogs. There was no significant difference (p = 1.000) in long-term outcome between conservatively and surgically treated dogs (78.9 and 75%, respectively). However, significantly more surgically treated dogs were non-ambulatory at presentation (9/17 vs. 5/24, p = 0.048) compared with conservatively treated dogs. This study suggests that conservative treatment may be appropriate for dogs with SEE that are ambulatory at presentation and that surgically treated dogs generally have good outcomes. Age may be a negative prognostic indicator as dogs with poor long-term outcomes were significantly older than dogs with a good long-term outcome (p = 0.048). A larger prospective randomized study may provide further insight on treatment and outcome of SEE in dogs.